2014
DOI: 10.1073/pnas.1323852111
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic IL-23 receptor signaling limits Th17 response through IL-22–mediated containment of commensal microbiota

Abstract: Significance Commensal microbiota are known to be required for the elicitation of host Th17 responses, which may mediate autoimmune diseases. Here, we demonstrate that the IL-23 pathway dynamically regulates the abundance of certain commensals and maintains barrier function. Barrier disruption results in systemic dissemination of microbial products, which invokes the IL-23 pathway, with both beneficial and potentially deleterious consequences. Through induction of IL-22, IL-23 contributes to barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 28 publications
6
90
0
2
Order By: Relevance
“…Further, we demonstrated that CF and WT mouse T lymphocytes produce IL-17 in response to IL-23 in a dose-dependent fashion, with CF mouse lymphocytes being particularly sensitive to IL-23 stimulation. This suggests T-cell dysregulation in CF, which is consistent with information published in the literature (6,42). The studies with…”
Section: Discussionsupporting
confidence: 91%
“…Further, we demonstrated that CF and WT mouse T lymphocytes produce IL-17 in response to IL-23 in a dose-dependent fashion, with CF mouse lymphocytes being particularly sensitive to IL-23 stimulation. This suggests T-cell dysregulation in CF, which is consistent with information published in the literature (6,42). The studies with…”
Section: Discussionsupporting
confidence: 91%
“…Mice with disrupted ILC3‐derived IL‐22 responses exhibit altered gut microbiota and increased susceptibility to experimentally induced colitis 49, 80, 81, 82. Most notably, expansion of segmented filamentous bacteria (SFB) – a canonical Th17‐inducing commensal species – occurs in the absence of ILC3 responses 49.…”
Section: Ilc3 Functions Under Homeostatic Conditionsmentioning
confidence: 99%
“…Mice lacking Ahr, IL-22, IL-23p19, or IL-23R have relative outgrowth of SFB and increased intestinal Th17 cells, and this appears to be due to a marked decrease in IL-22-producing immune cells, particularly ILC3s (92)(93)(94). IL-22 is critical for maintaining intestinal barrier function, and in the absence of IL-22, SFB increase in relative abundance, leading to an increased may lead to altered immune responses and promote autoimmunity.…”
Section: Il-23 and Autoimmunitymentioning
confidence: 99%
“…This appears to be directly mediated by the salt-sensitive kinase, frequency of Th17 cells in both the intestine and distal secondary lymphoid tissue (93,95,96). IL-23-induced IL-22 also appears to be critical for prohibiting microbiota from entering normally restricted anatomical compartments, as mice deficient in both IL-23R and RAG2 have elevated levels of LPS in both the spleen and liver (93). Furthermore, selective depletion of ILCs results in systemic dissemination of Alcaligenes spp., a normal enteric commensal (97).…”
Section: Il-23 and Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation